"Old dog, new tricks": the lone pair effect inducing divergent optical responses in lead cyanurates containing π-bonds. Issue 5 (7th January 2020) - Meng, Xianghe; Kang, Kaijin; Liang, Fei; Tang, Jian; Lin, Zheshuai; Yin, Wenlong; Xia, Mingjun
Abstract : The stereochemically active lone pair effect of Pb 2+ and induced narrower bandgaps were elaborated in Pb3 (HC3 N3 O3 )2 (OH)2 for the first time. Abstract : The stereochemically active lone pair (SCALP) effect of Pb 2+ plays a vital role in enhancing the nonlinear optical response and engineering the band gap of lead-based materials with intriguing properties. Herein, we combined SCALP Pb 2+ cations and π-conjugated (HC3 N3 O3 ) 2− anions into one structure to investigate the tunable optical properties. Two lead cyanurates, namely, Pb3 (HC3 N3 O3 )2 (OH)2 (I) and its partly cadmium-substituted analog Pb2 Cd(HC3 N3 O3 )2 (OH)2 (II) were grown by the mild hydrothermal method. They exhibited greatly narrowed bandgaps and enhanced optical anisotropy resulting from the SCALP effect. In addition, divergent optical responses induced from the involved Pb (6s 2 6p 2 ) and Cd (4d 10 5s 2 ) were elaborated by a combination of experimental and theoretical analyses.